(untitled) (Research, Society and Development, 2022)
Achondroplasia is a rare disease of autosomal dominant inheritance, caused by the replacement of the amino acid glycine by arginine at position 380, affecting the fibroblast growth factor 3 receptor (FGRF-3). Its characteristics are evident since intrauterine life, and are detectable by ultrasound. The aim of this study is to determine the main clinical changes in patients with achondroplasia. A review of the medical records of patients diagnosed with Achondroplasia was carried out from 2002 to 2018, followed up at the medical genetics service of a tertiary hospital in the state of Ceará - Brazil. Twenty-eight patients were included in the study. The average age of the patients, at first evaluation, was 26 months (0,5-140). 3 patients (10.7%) were born preterm, however 100% of the patients had a 5-minute APGAR above 7. The patients’ main delays concerned to sitting (18%), walking (11%) and talking (11%). The most prevalent abnormalities were macrocrania, short limbs, hyperlordosis, trident fingers and breathing problems. In this study, a slight predominance of males was observed and, despite the delay in neurological development milestones, there were no changes in neurological and cognitive functions in most cases. The clinical changes observed correspond to those already known in the literature and should be recognized by the general practitioner, as well as by other professionals involved in the care of patients with achondroplasia, aiming at an early diagnosis of this condition for adequate treatment and genetic counseling.